Temporary Detention in Investigating Criminal Cases and Their Legal Consequences - Akli, Zul; Abidin, Zainal; Nasir, Muhammad; Johari, Johari; Zulkifli, Zulkifli (International Journal Labs, 2021)
Background: In the provisions of Article 28(A) of the 1945 Constitution it is stated that